REKRUT MENCALON PEGAWAI NEGERI SIPIL - Elvira Maria E.21109095 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Background of the Civil Service recruitment is a civil servant who enters the retirement age employees that mutations in the structural positions, as well as functional, transfer out of the area, the employee who died, the employee who quit with honor or not with respect so that the resulting short-staffed. For the purpose of this study is to describe the process of Recruitment / Procurement CPNS with the principle objective, Transparent, Competitive and Accountable with a qualitative approach. These results indicate that the implementation is quite good recruitment needs and objectives, formation composed of each on education, according to the principles Recruitment Process: Objective, Transparent, Competitive and Accountable namely a process activity to determine graduation, with a pure assessment test results / in accordance with the actual reality and publicly accountable and professional so that information is easily accessible and accurate so as to produce employess. Fore expected to be further enhanced the executive recruitment process according to the principles and rules and regulations applicable Perundnag. Formation composed prioritize basic service personnel (health workers) with Technical Workers, in stages, to be submitted to the Minister of State for Administrative Reform and Bureaucratic Reform as policy makers, the State Personnel Board as Technical Administrative Appointment as a civil servant. Implementation should in the first quarter and the second, the implementation of the final quarter was difficult because they have to account for expenditure incurred due to these activities also paperwork proposal materials demand Employee Identification Number. Keywords: objectivity, recruitment, employee